EVALUATION OF THE POTENTIAL ROLE OF AQUEOUS LEAVES EXTRACT OF AVERRHOA CARAMBOLA FOR IN VITRO ANTICANCER STUDIES - SRILEGA I; KAVITHA M (Innovare Journal of Life Sciences, 2024)
Objective: Averrhoa carambola is known as a tree. Averrhoa carambola leaves are commonly used in Ayurvedic and traditional Chinese medicine is used for inflammatory skin disorders and fungal skin infections. The leaves of star fruit are rich in Vitamin C and bioactive compounds such as phenols and flavonoids abundant sources of antioxidants. Methods: The qualitative phytochemical study of these plant extracts indicates the presence of tannins, saponins, flavonoids, alkaloids, proteins, and phenol. The herb has been used traditionally from antiquity, in the treatment of neurological health, memory issues, and breast cancer. It chiefly possesses the pharmacological study. Results: Plant explains about antibacterial, antioxidant, antifungal, anticatalytic, and antiviral activities. The work is an endeavor to explore and assemble the various pharmacological action and pharmacognostic aspects of the leaves A. carambola reported to date. Conclusion: The current research has shown that natural sources have therapeutic properties without much toxicity. This potential of plants is due to the presence of secondary metabolites. The results prove that A. carambola leaf extract has antioxidant, antibacterial, and antifungal activity. In addition to this, the present investigation revealed that A. carambola leaf extract can act as a potential drug for treating breast cancer.